(untitled) (Hekima Review, 2023)
The winds of change have been rocking the boats of Churches and ecclesiastical communions for a while now. There have been calls for reform, but one would wonder whether the term reform and its correlative re-form are the same or disparate. Does the call for reforms means also re-form and vice versa? This article seeks clues in the Hebrew Bible, replete with narratives on reforms and ref-form. We shall approach the texts synchronically by deducing the message and applying them to the reform discourse.